Uso de etograma na conservação de Jacutingas - Aburria jacutinga (Spix, 1825) (Galliformes: Cracidae) : comportamento antipredatório e avaliação de dieta como subsídio para a criação e soltura - Rivera, Douglas Nazareth (2016)
The jacutinga (Aburria jacutinga) is a large frugivore bird in the process of extinction primarily by hunting and habitat destruction. Endemic of Atlantic Forest, currently has limited distribution and isolated populations. For this reason, is the focus of some conservation programs aimed at the captive-breeding for later release and/or reintroduction into unique environments of the species. This study used behavioral assessments in a pre-release rearing system, and promoted training aimed at food aspects and predator recognition. It was observed 31 jacutingas and produced a ethogram with 68 behavioral acts, grouped into eight categories. After, were held training sessions to food type and antipredator type. Food training intended to assess food acceptance and promotion of foraging behavior. It offered 32 different food items, six of which were not accepted. It was noticed diversification acceptance of food items, especially fruits and seeds up to 20 mm, but also leaves and flowers. For foraging behaviors observed, as the capture and handling of food items, they are performed only when the jacutinga achieves the item with its beak. This may be the reason for the jacutingas remain for long periods in the same tree, when it finds items for their food. For the antipredator training it were used three models of predators: a feline (Leopardus tigrinus), one raptor (Pseudastur polionotus) and domestic dogs. In these training sessions were observed eight jacutingas. Both training sessions were positive, with behavioral responses of surveillance and defense to the models used. Also, memory tests were performed where the same models were presented for jacutingas, after 30 days of training. The results of the memory tests indicate that there was a learning result of antipredator training. The jacutingas showed the expected responses (similar to the training) when the models were presented. It highlights the importance of the work, because the results are assisting in the rehabilitation process of individuals to be used in future releases. The entire process developed in this study is being used experimentally as a pilot in" Protocolo de Soltura de Jacutingas " coordinated by SAVE Brazil. The training and the tests are intended to increase the survival rate of birds used in release programs, through techniques that enhance and/or induce the production of behaviors that express survival skills in nature; in this case, foraging skills and predator recognition as behavioral indicators to obtain individual fitness.